PENGARUH IMPLEMENTASI SUPPLY CHAIN INTEGRATION, JUST IN TIME PURCHASING DAN JUST IN TIME MANUFACTURING TERHADAP LOGISTICS PERFORMANCE - NUNO SUTRISNO (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2014)
The purpose of this research was to know whether there were direct influence between the implementation supply chain integration, just in time purchasing and just in time manufacturing toward logistic performance on Supplier Companies (Transportation Cost, Material Handling Cost and Inventory Level)”. This research used 30 supplier company of PT. Toyota Manufacturing Indonesiapremisesaredetermined based on purposive sampling. Data were analyzed using Structural Equation Modeling (SEM). The result of this research concludes that the implementation of Supply Chain Integration and Just in Time Purchasing directly influence Logistics Performance, meanwhile, the implementation of Just in Time Manufacturing indirectly impact Logistics Performance.